Effects of early-life lactoferrin intervention on growth performance, small intestinal function and gut microbiota in suckling piglets. Issue 9 (8th August 2019) - Hu, Ping; Zhao, Fangzhou; Zhu, Weiyun; Wang, Jing
Abstract : The early postnatal stage is a critical period for suckling animals in developing intestinal function and stabilizing gut microbiota. Abstract : The early postnatal stage is a critical period for suckling animals in developing intestinal function and stabilizing gut microbiota. Lactoferrin (LF) plays a critical role in promoting gut development and regulating gut microbiota. This study investigates the impact of early-life lactoferrin (LF) intervention on the growth performance, small intestinal function and gut microbiota in suckling piglets. Sixty suckling piglets (1.51 ± 0.05 kg) obtained from six sows (10 piglets per litter) were assigned to a control (CON) group and an LF group in each litter, which were sow-fed. Piglets in the LF group were orally administered 8–12 mL LF solution (0.5 g per kg body weight per day) for a week, and piglets in the CON group were orally administered the same dose of physiological saline. Six piglets ( n = 6) from each group were euthanized on days 8 and 21. The early-life LF intervention increased growth performance, with higher villi height of the jejunum and greater disaccharidase activity of the jejunum and ileum ( P < 0.05). Diarrhoea incidence decreased in the LF group from day 1 to day 7 ( P < 0.05). Urinary lactulose–mannitol ratios decreased in the LF group, whereas the gene and protein expressions of jejunal occludin increased in the LF group on day 8 and day 21, and higher gene and protein levels of ileal occludin were observed on day 8 ( P < 0.05). Additionally, the LF piglets had lower concentrations of IL-1β and TNF-α, and higher concentration of IL-10 in the jejunum ( P < 0.05). For the ileum, higher concentration of IL-10 and lower concentration of TNF-α were observed in the LF group ( P < 0.05). LF piglets had a greater abundance of Lactobacillus and lower abundance of Veillonella and Escherichia-Shigella in the jejunum on day 8 ( P < 0.05). In the ileum, the abundance of Actinobacillus was decreased in the LF piglets on day 8 and day 21 ( P < 0.05). The early-life LF intervention enhanced the growth performance and decreased diarrhoea incidence in the suckling piglets by promoting the development of intestinal function and changing the microbiota in the small intestine.